(3GdOQhY GdMUjfI GdOGhQhjI aj GdJhSd HGdSGOI GdHOhjI hGdCMeOjIs - (3YHO GdeMehO Hf fhQ GdOGFe NdjaIs
(3ChdgG (B:s
(3jG YGdekG HGdMGd jG Gddg jG edLC GdeVWQ jGA TGg jG Mi jG bjhe jG bQjH SejY jG bGOQ jG eLjH s
(3BNQgG (B:s
(3Udi Ydjg Gddg eY AGdg eY CUMGHg Cgd GdWQjb GdeJHY hbGd eMehO CjG QHGg jG YGdekG HGdMGd jG Gddg s
(3hGdbUjOg ajgG GSJYGfg HGdSGOI GdcQGe ai Cf jSJLjH Gddg ddSGFd MGLJg def NdGd QLGdg GdCHQGQs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQI GdYfhGf (B:s
(3fXes
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs